Voice of a Nation: Waldjinah, Langgam Jawa, and the Gendered Politics of Postcolonial Music in Indonesia - Putri, Trikaloka Handayani; Zainsty, Arly Yanatri (Harmonia : Journal of Music and Arts, 2024)
Langgam Jawa, a subgenre of keroncong rooted in Javanese musical and poetic traditions, serves as a crucial expression of postcolonial cultural identity in Indonesia. This article investigates the role of Waldjinah, the genre’s most iconic figure, in shaping the gendered and national aesthetics of Langgam Jawa through her musical style, lyrical themes, and media representation. Employing feminist musicology, postcolonial performance theory, and reception analysis, this study draws on archival recordings, televised performances, and song lyrics to explore how Waldjinah’s vocal ornamentation and public persona mediated Javanese femininity within state-sanctioned cultural frameworks. Analytical attention is given to her use of undul-usuk ornamentation, integration of macapat-inspired lyricism, and curated visual aesthetics across different media platforms. The results demonstrate that Langgam Jawa’s hybrid musical structure combining diatonic instrumentation with traditional Javanese idioms enabled Waldjinah to navigate and subtly challenge dominant gender and cultural norms. Her work was simultaneously supported by state institutions and shaped by them, contributing to the canonization of Langgam Jawa as part of Indonesia’s national musical identity. This research concludes that Waldjinah’s artistic trajectory reflects the complex interplay between individual agency and institutional power in the construction of musical canons. Her legacy exemplifies how music functions as a site of gendered, regional, and national negotiation in postcolonial contexts. The findings suggest a need for further inquiry into the evolving interpretations of Langgam Jawa in the digital age, particularly among younger female performers.